Electrically Active and Inactive Single Grain Boundaries in Semiconducting BaTiO3. Issue 10 (20th July 2015) - Yoon, Seok‐Hyun
Abstract : Bi‐crystal specimens were prepared from Nb and Mn‐doped BaTiO3 poly‐crystals with giant grains of millimeter order in size, and the resistance ( R ) versus temperature ( T ) characteristics of these individual grain boundaries was investigated. The electrically active grain boundaries that show normal positive temperature coefficient resistor (PTCR) behavior had no second phases or they were partially distributed along boundaries. On the other hand, electrically inactive grain boundaries that show flat R‐T characteristics were also observed, where continuous Ti‐rich second phases of Ba4 Ti12 O27 could be detected. Different interface state density and its resultant R – T characteristics were observed for each individual active boundary, which indicates the degree of oxidation and the formation of potential barrier can be different depending on the character of the grain‐boundary plane. The resistance of inactive boundaries was determined by that of insulating second phase showing negative temperature coefficient resistor (NTCR) behavior. These results demonstrate that continuous second phase surrounding a grain deactivates the electrical properties of grain boundary, and thus should be distinguished from insulating depletion layer near grain boundary.